Regulatory Mitigation of Digital Bank-Run Risk in Indonesia’s Rupiah Digital: A Normative Legal Framework for Monetary and Financial Stability - Fatahillah, Mochamad Ilham; Kusumaningrum, Adi; Dewantara, Reka (International Journal of Business, Law, and Education, 2026)
Indonesia’s development of the Rupiah Digital, the country’s prospective central bank digital currency (CBDC), offers a strategic opportunity to modernise the payment system, strengthen monetary sovereignty in the digital sphere, and broaden access to central-bank money. Yet a retail CBDC also creates a distinctive financial-stability risk: a digital bank run in which depositors rapidly migrate funds from commercial bank deposits to risk-free central-bank liabilities. This article examines the urgency of regulating digital bank-run risk in the circulation of the Rupiah Digital and reconstructs an ideal regulatory model for Indonesia. Using normative legal research with statutory, conceptual, and comparative-institutional approaches, the article analyses the 1945 Constitution, the Currency Law, the Banking Law, the Bank Indonesia Law, the Financial System Crisis Prevention and Resolution Law, the Financial Services Authority Law, and Law No. 4 of 2023 on Financial Sector Development and Strengthening. The study finds five structural gaps in Indonesia’s existing legal framework: the absence of retail CBDC holding limits, tiered remuneration rules, digital-run crisis protocols, CBDC-specific emergency liquidity arrangements, and ecosystem-wide cyber-risk governance. These gaps are legally significant because the Digital Rupiah’s status as a direct liability of Bank Indonesia may accelerate systemic disintermediation under conditions of panic. The article proposes a five-pillar regulatory architecture comprising dynamic holding limits, tiered remuneration, statutory crisis protocols and circuit breakers, an emergency CBDC liquidity facility, and cyber-risk governance. It argues that these safeguards should be enacted at the statutory level and integrated into the Financial System Stability Committee framework before full public deployment of the Rupiah Digital.